HABITUS DAN ARENA INTELEKTUAL RASYID RIDHA : Telaah Pemikiran Konsep Sunnatullah dalam Tafsir al-Mannâr - Mukhamad Agus Zuhurul Fuqohak (STAI AL-ANWAR SARANG, 2024)
Interpretations that explore social and reformist elements in understanding the verses of the Qur’an remain scarce. Social themes are usually used to portray religious activities contained in the study of the Living Qur'an. In fact, the ideal interpretation is to touch on clear social concepts as Rasyid Ridha's view in Tafsir al-Mannâr. This research employs a descriptive analysis method and applies Pierre Bourdieu’s habitus theory to examine the theological and sociological foundations of the Sunnatullah concept in Tafsir al-Mannâr by M. Rasyid Ridha. Ridha rejects mystical interpretations and the world of Sufism. He prioritizes rational and reformist interpretations. According to him, it is more useful and provides a positive contribution to the progress of Islam. This study also reveals Ridha's habitus and intellectual arena in implementing the Sunnatullah concept. Ridha’s habitus was shaped by his strong educational background and exposure to modern Islamic thought. His intellectual arena was formed through his close association with M. Abduh, his leadership in the journal al-Mannâr, and his authorship of Tafsir al-Mannâr. While his intellectual arena emerged in his opportunity to accompany M. Abduh, holding the journal al-Mannâr and writing the book Tafsir al-Mannâr. Ridha transformed the concept of Sunnatullah from a mere thematic subject in Tafsir Maudhu’i into a foundational interpretive framework for achieving a social reformist exegesis.